COMPOSITION, LENGTH-WEIGHT RELATIONSHIP, AND FISHING GROUND OF SHARKS LANDED AT PPS CILACAP, CENTRAL JAVA - Krisnafi, Yaser; Dian Novianto; Syam Baharuddin Sahid; Ratih Purnama Sari (Bogor Agricultural University, 2024)
This study was conducted to analyze the catches of sharks, such as composition, length-weight relationship, and to determine the distribution of shark fishing areas. Every fishing activity has by-catch issues. Fishers commonly catch sharks as by-catch. These fishing activities will harm the shark ecosystem in the waters. This research was conducted in March – May 2021 at PPS Cilacap. The results of this study showed that A. superciliosus (paitan shark) was a common catches and its total catch was 1,820 kg. The next common catch was Carcharhinus falciformis and the total catch was 723 kg. The lowest catch was the Carcharhinus sorrah shark (sorrah shark) and its total catch was 16 kg. The growth of Carcharhinus falciformis was negative allometric because b-value <3. Meanwhile, the growth of A. superciliosus is positive allometric because b-value was > 3. Length-weight relationship of Carcharhinus falciformis and A. superciliosus was isometric, which means that the growth between length and weight is balanced. Shark fishing areas are located at coordinates 8º - 15º South and 100º - 111º East. The area of shark fishing is at coordinates 8º - 10º South and 108º - 110º East. Keywords: Composition, Length-Weight Relationship